THE ROLE OF DESIGNERS IN THE SOCIAL DESIGN DEVELOPMENT IN INDONESIA - Indriati, Lisa (VCD, 2021)
Designers have been active promoters who campaign for the wellbeing of life through the convenience and practicality created through design (Manzini, 2015). However, it has only recently been realized that the positive intentions discovered to be unsustainable that leads society to become very consumptive, thus causing a negative impact on the social, economic, and environmental problems we face today. Designers who are contributing to this problem need to be part of the solution, therefore it is necessary to develop tools or methodological frameworks to help designers get new ideas, develop solutions and utilize technology to create engaging sustainability initiatives for society. The major problem that society faces today is the lack of sensitivity to sustainable ways of living. Social problems play an important role in initiating the desired change, the power of design as a means to change behaviour into interests among the people, especially interests in the field of sustainable design or what is now commonly referred to as social design. The main purpose of the social design was to initially design products that require the least energy to produce and can be recycled. However, the development of massive industrialization produces a negative impact on the environment and society so that the development of social design shifts focus on things that affect change, the design must be able to change user behaviour. Keyword: social design, social impact, community, responsibility, sustainability.